Trends in Technological Innovation in Education During a Time of Pandemic Disruption: Examining The Perspective of Teaching Digital Pedagogy - Syanti Dewi Harahap; Jimmi Jimmi; Petrus Jacob Pattiasina; Zulvia Trinova; Antono Damayanto (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2022)
Since the world has been disturbed by the increasing impact of Covid-19, various countries have applied distance learning, responding to the pandemic policy on an international scale. The author believes that the learning of technological innovation for Indonesia is different from that of developed countries, so this study tries to understand the digital pedagogical perspective of teaching. A series of successful electronic literature searches were carried out on several scientific journal publications, books, and other website literature to get the intended understanding. The data that we have obtained are then analyzed in-depth, involving critical coding and high evaluation to obtain understanding and conclusions that can answer the core questions of this study. We used all data from secondary data, namely scientific evidence published between 2010 and 2021. Then the design of this study was in a descriptive qualitative system under a phenomenological approach, an effort to explore data as widely as possible. After discussing the results, we included that pedagogical technology, which is a method that discusses how teachers handle their duties assisted by technological innovation. However, the pedagogy also helps teachers become student learning facilitators by using existing technological facilities to improve learning outcomes. While at the same time developing students' potential even though they are being afflicted with learning disorders due to pandemics. We hope this result can be a contributing input for further studies.